All-in-fiber fabrication of cladding devices and components using femtosecond laser pulses - Ioannou, Andreas; Theodosiou, Antreas; Caucheteur, Christophe; Kalli, Kyriacos (My University, 2020)
Femtosecond (fs) lasers are well suited for high-resolution inscription in transparent materials of all types, and in particular optical fibres. The 'inscribe and step', Plane-by-Plane (Pl-by-Pl) inscription method enables the fabrication of components, such as cladding waveguides (CWGs), cladding Mach-Zehnder interferometers (MZIs) and embedded waveguide Bragg gratings (MZI-FBGs), using the same key femtosecond laser parameters. The cladding waveguides structures were inscribed in such proximity for the fiber core that allowed evanescent coupling to occur. Having this operational principle, the compound cladding sensor has minimal effect on fiber strength, leading to a robust sensing device. Furthermore, the versatile femtosecond laser-inscribed cladding waveguides and ultra-compact MZIs that can support functional, integrated fibre Bragg gratings (FBGs). This method ensures a single inscription process, offering reliability and repetition in component manufacturing. This hybrid configuration can measure multiple parameters using the same demodulation equipment, with very high sensitivity while minimizing cross sensitivity issues. We focus on the response to changes in temperature, strain, bend, and relative humidity of the developed components.
Keywords: Femtosecond laser inscription; Fibre optics sensors; Fibre Bragg gratings; Cladding components; Microstructure fabrication; Optical design and fabrication